Construction and Application of Multi-dimensional Quality Evaluation Model of Government Reply - FU Rao; LIU Huilan (Journal of Harbin University of Science and Technology, 2023)
With the development of smart government, there are problems about quality and efficiency of reply. According to the performance evaluation theory of government affairs, the timeliness, relevance, exhaustion, information intensity, interpretability and normative of government reply are studied, which combined with ALBERT and other algorithms. According to the potential spatial representation extracted by Auto Encoder and the representation weight determined by Entropy Weight Method, a comprehensive evaluation model of the quality of reply is realized. The model is used to analyze quality of reply about business consultation of customs. The weights of representation are 0. 098 , 0. 436 and 0. 466 respectively. The reply with a normalized score between 0. 2 and 0. 4 is the largest , accounting for 39. 7% . The consistency degree between model score and manual score is 0. 777 with randomly selected reply, and the MSE is 0. 035 , indicating that the model could reflect truly quality of reply.